Interference with the Mannose Binding and Epithelial Cell Adherence of Escherichia coli by Sublethal Concentrations of Streptomycin - Eisenstein, Barry I. (1979)
When Escherichia coli was grown in sublethal concentrations of streptomycin, mannose binding activity and epithelial cell adherence of the E. coli cultures at stationary phase were significantly reduced in the drug-grown organisms. In a strain whose minimal inhibitory concentrations was 30 μg/ml, the percentage of reduction in mannose binding activity was dose related over a range of concentrations between 0.5 and 10 μg/ml streptomycin. Concomitant with the drug-induced suppression of mannose binding activity, antigenic and ultrastructural alterations on the surface of the drug-grown organisms were observed by agglutination tests and electron microscopy, respectively. The streptomycin effect was reversible, required actively growing organisms, and was most apparent in the early log-phase of growth. High doses of antibiotic were ineffective when added to cultures which had acquired mannose binding activity. An isogenic derivative with high-level resistance to streptomycin was obtained as a single-step mutation from the test E. coli strain. Whereas the isogenic mutant possessed mannose binding activity and adhering ability similar to the parent strain, it was resistant to the streptomycin-induced suppression of the two activities at enormous concentrations (up to 10,000 μg/ml) of streptomycin. Taken together the results suggest that the suppression of epithelial cell adherence and mannose binding activity of E. coli grown in sublethal concentrations of streptomycin is a result of classic mechanisms of drug action upon the bacterial ribosome. The results support the possibility that antibiotics may act through mechanisms other than inhibition of growth and bacterial killing to eradicate bacteria from mucosal surfaces.